Actuating and sensing mechanism of embedded piezoelectric transducers in concrete. (3rd July 2020) - Yu, Haifan; Lu, Linjun; Qiao, Pizhong; Wang, Zijian
Abstract: The generalization and monitoring accuracy of wave propagation method using embedded piezoelectric transducers in concrete heavily depend on actuating and sensing mechanism. In this study, the actuating and sensing mechanism of extensional mode piezoelectric transducers is investigated. The theoretical analysis results reveal that the sensing mechanism is much different from the actuating mechanism and influenced not only by the piezoelectric constants and sizes of transducers but also by the placement angle of piezoelectric patches and the type of stress wave acting on the sensors. The actuating and sensing mechanism of piezoelectric transducers embedded in concrete is then numerically and experimentally studied, and the effects of placement schemes of transducers on the stress wave generation, propagation and reception are discussed. The transmission effect is taken into consideration to illustrate the energy transfer from the transducers to concrete. Good agreements between the numerical and experimental results indicate that both the placement schemes of transducers in concrete and the propagation direction of stress waves have significant influence on the amplitude of received signals. The envelope peaks of two typical cases with the piezoelectric patches placed along 0° and 90° are compared to further manifest influence of the placement angle on the actuating and sensing mechanism of transducers. The recommendations for the placement schemes of transducers based on target signal selection are given. The clarifications on the stress wave propagation of embedded piezoelectric transducers in concrete and their sensing and actuating mechanism presented can better explain some unusual phenomena observed and improve the effectiveness and monitoring accuracy of embedded piezoelectric transducers in material property assessment and structural health monitoring of concrete.